ON THE READINESS OF FIRST-YEAR STUDENTS FOR PROJECT-ORIENTED TRAINING IN HIGHER EDUCATION - Medvedeva, Irina; Martynyuk, Oxana; Pan’kova, Svetlana; Solovyova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The training of a graduate with project thinking is one of the trends in modern higher education. Specialist with soft skills is in demand by society. The formation of soft skills is facilitated by using project technologies in training. In this regard, it seems important to identify the level of readiness of freshmen to project-oriented training.The purpose of this article is to analyze the readiness of first-year students of the Institute of Mathematical Modeling and Game Practice of Pskov State University for project-oriented study at a university. The research used the following methods: analysis of the scientific literature on the research problem, observation, expert evaluation, questioning, and statistical analysis of the results. In the process of research, (a) the need for an input assessment of freshmen readiness for project activities was substantiated, (b) the components of students' readiness for project-oriented training were identified, (c) the selected components were evaluated during the training project carried out by freshmen, (d) the results were analyzed.